Sumoylation in Lens Differentiation and Pathogenesis - Xiang, J.-W.; Chen, Z.-G.; Gong, L.; Xiao, Y.; Qing, W.-J.; Wang, L.; Hu, X.-H.; Huang, Z.-X.; Qi, R.-L.; Yang, T.-H.; Arrigo, A.-P.; Zhang, L.; et al. (Current Molecular Medicine, 2016)
Sumoylation, a post-translational modification discovered over a decade ago, turns out to be a very important regulatory mechanism mediating multiple cellular processes. Recent studies from our laboratory and others also revealed that it plays a crucial role in regulating both differentiation and pathogenesis of the ocular lens. This review will summarize these progresses.
Keywords: sumoylation